Relationship between Bone Mineral Density and Parity in Women of Reproductive Age Group - Jesmin, Fatima; Begum, Fatima; Enamullah, CAHM; Alam, Faridul (Bangladesh Journal of Nuclear Medicine, 2018)
Objective: The objective of this study was to assess the relationship between Bone Mineral Density (BMD) and parity in women of reproductive age group. Materials and methods: A cross sectional analytical study was carried out where the study population was women of reproductive age group (15 to 49 years of age). A total of 180 women were included as study subjects and the sampling technique was non random sampling. The study population was selected from healthy women of reproductive age group. Data about age, height, weight and history of parity were taken. BMD was measured by DEXA. Then relationship between BMD and parity were analysed. Results: In this study, a large number, 79 (43.9%) of participants were in age group of 29-38 years with mean± SD 35.46±6.75 years. Association between BMD and age of the study subjects represented that values of BMD decreased with increasing age (P<0.05). Bivariate analysis between BMD and parity revealed that values of BMD at lumbar spine and femur were associated with parity and it was also showed that the BMD of nulliparous women and one-to-two parity groups were significantly higher than multiparous (≥3 parity) women (P<0.05). Conclusion: From overall analysis of this study it can be concluded that BMD at lumbar spine and femur in women of reproductive age group was negatively associated with number of parity. Bangladesh J. Nuclear Med. 18(2): 117-120, July 2015